2012
DOI: 10.1177/2041731412455354
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation directs engineered cardiac tissue to an age-matched native phenotype

Abstract: Quantifying structural features of native myocardium in engineered tissue is essential for creating functional tissue that can serve as a surrogate for in vitro testing or the eventual replacement of diseased or injured myocardium. We applied three-dimensional confocal imaging and image analysis to quantitatively describe the features of native and engineered cardiac tissue. Quantitative analysis methods were developed and applied to test the hypothesis that environmental cues direct engineered tissue toward a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 55 publications
(114 reference statements)
1
63
0
Order By: Relevance
“…Other studies support this observed correlation between changes in cellular function and altered localization of Cx43. For instance, exogenous electrical pacing, which has shown improvement in functional maturation of cardiomyocytes, has resulted in increased presence of Cx43 structures within engineered rat myocardium [49] as well as increased Cx43 along the membranes of individual neonatal rat cardiomyocytes relative to non-stimulated myocardium [50]. Similarly, cyclical mechanical stretching of cardiomyocytes has been shown to enhance overall Cx43 presence [51], which can include increased gap junction expression at the poles of each cell [52].…”
Section: Discussionmentioning
confidence: 97%
“…Other studies support this observed correlation between changes in cellular function and altered localization of Cx43. For instance, exogenous electrical pacing, which has shown improvement in functional maturation of cardiomyocytes, has resulted in increased presence of Cx43 structures within engineered rat myocardium [49] as well as increased Cx43 along the membranes of individual neonatal rat cardiomyocytes relative to non-stimulated myocardium [50]. Similarly, cyclical mechanical stretching of cardiomyocytes has been shown to enhance overall Cx43 presence [51], which can include increased gap junction expression at the poles of each cell [52].…”
Section: Discussionmentioning
confidence: 97%
“…19 Because of the improvements observed in construct development, electrical stimulation has been used in a number of other studies as a method of developing functional engineered cardiac constructs. [20][21][22] Though both electrical and mechanical stimulation are standard methods of physical stimulation in cardiac construct development, to date, there have been no direct comparisons of the differences between electrical and mechanical stimulation. Attempting to compare published data is also difficult as these studies have been done in different systems with different measures of improvement.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the mechanical stimulation studies often looked at twitch force and related properties, 8,23,24 while electrical stimulation studies generally have assessed improvement through fractional area shortening, excitation threshold, and maximum capture rate. 22 These differences have inhibited the discussion of a comparison between electrical and mechanical stimulation, as well as any study on their interplay and the potential effects of a combined stimulation approach on the development of functional engineered heart tissue. Though bioreactors that have both electrical and mechanical stimulation capabilities have been created previously, 14,25,26 to date, only one study has looked into the effects of combined electromechanical stimulation in cardiac engineered tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Next to features such as culture medium perfusion, the presence of hemoglobin via oxygen carriers in the culture medium or the acting of cyclic stretch, electrical field stimulation is the most important to mimic heart tissue. Electrical field was used for development of in vitro models of arrhythmia, investigation of cardiac phenotype or analysis of cells migration and orientation (Bian and Tung, 2006, Sathaye et al, 2006, Kong et al, 2005Xu et al, 2014, Nunes et al, 2013, Lasher et al 2012, Kujala et al 2012). Moreover, electrical stimulation can be used to enhance function of the cardiac cells and the formation of synchronously beating tissue (Radisic et al, 2004Hirt et al, 2014.…”
Section: Heart Tissue Culture and Toxicity Analysismentioning
confidence: 99%